The Effectiveness of Think Talk Write Model to Increase Students’ Learning Motivation at Junior High School - Choirun Nisa; Zaky Anwar; Syaiful Mustofa (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study aims to determine the effectiveness of the Think Talk Write model in increasing learning motivation at Junior High School Muhammadiyah 1 Malang. Researchers used a quantitative approach with 23 research subjects in class VIII students of Junior High School Muhammadiyah 1 Malang. In this study researchers use Quasi Experiments because researchers use control classes and experimental classes. Methods of data collection include questionnaires and tests. This study's data analysis used a sort of comparative analysis, namely, a comparison of pre- and post-test values (sample t-test related). This study found a significant difference between pre- and post-test scores, with a sig value of 0.000 less than 0.05 (0.000 0.05) indicating a difference between pre- and post-test learning outcomes, and an N-Gain test indicating a moderate increase in scores (0.62). Based on the data analysis that has been conducted, there is an improvement in students' learning motivation after using the Think Talk Write model, thus the Think Talk Write learning model can be considered as an alternative in the learning process.